Caregivers as Interventionists and Trainers: Teaching Mands to Children with Developmental Disabilities - Loughrey, Tara Olivia (Anal Verbal Behav, 2014)
We evaluated the use of behavioral skills training (BST) to train caregivers to conduct procedures commonly associated with mand training. We trained two caregivers on the following procedures: (a) conducting preference assessments, (b) delivering preferred items contingent on appropriate behavior, (c) capturing and contriving motivating operations, (d) conducting probes to assess the child’s current mand repertoire, (e) errorless prompting procedures using echoic prompts, (f) vocal shaping, (g) collecting data, and (h) correcting errors. We also assessed whether a trained caregiver could in turn train their spouse on these procedures. We evaluated the effects of the intervention on the frequency of child spontaneous and prompted mands. The three caregivers performed near zero percent accuracy during baseline but increased to above 80 % accuracy with training, and high performance persisted during most maintenance probes. These results were replicated for the parent who received training from their spouse. In addition, spontaneous mands were occurring more frequently than prompted mands by the end of the study. The implications of caregivers implementing mand training procedures based on Skinner’s analysis of verbal behavior are discussed.